Insights into the roles of aerosol soluble iron in secondary aerosol formation. (1st February 2023) - Lei, Yali; Li, Dan; Lu, Di; Zhang, Tian; Sun, Jian; Wang, Xin; Xu, Hongmei; Shen, Zhenxing
Abstract: Aerosol soluble iron (Fe) is crucial in the biogeochemical cycle and atmospheric processing. In this study, soluble Fe and their solubility in fine particles (PM2.5 ) were investigated over Xi'an, China to insight the iron sources and the roles in aerosol formation. Our results showed that most Fe in PM2.5 was insoluble (Fe solubility: 25.5 ± 11.3%). Seasonal variations exhibited that the highest soluble Fe(II) showed in winter (308.9 ng m −3 ) and the highest Fe(III) levels were in summer (116.3 ng m −3 ). Source identification of soluble Fe illustrated that industrial coal combustion contributed most in summer, whereas mineral dust, biomass burning, and coal combustion dominated in spring, autumn, and winter, respectively. Moreover, strong correlations between soluble Fe and water-soluble inorganic ions suggested soluble Fe is related to not only primary sources but also secondary formations. Furthermore, a negative correlation (R = −0.56) was observed in winter between Fe(III) and SO4 2−, indicating that the oxidation pathway of Fe(III) catalysis should play a vital role in sulfate formation in winter. In addition, secondary brown carbon presented positive correlations with soluble Fe(II), while negatively correlated with soluble Fe(III), potentially suggested an important pathway for the formation of secondary BrC. Our study provides a broader understanding of Fe solubility and their roles in atmospheric chemical processing. Graphical abstract: Image 1 Highlights: Field observation was conducted to reveal the role of soluble Fe in secondary aerosol formations. Fe(II) was the highest in winter, while the highest Fe(III) was in summer. Both biomass burning and coal combustion contributed to soluble Fe. Fe-chemistry played a vital role in winter sulfate and secondary BrC formations.